Contemporary Sport Policy in Bulgaria – Priorities, Problems and Future Prospects for Tackling Inactivity : focus on sport participation - Filipov, Nikolay (2018)
Participation in sport and physical activity is considered as an important part of a healthy life and different countries have utilized it with varying success not just to achieve sport-specific objectives but also to improve public health. A key factor for having a physically active nation is the sport policies that a country has developed. In Europe, the differences in sport participation vary immensely with southern- and south-eastern European countries appearing as least active. This study has analysed contemporary sport policy in Bulgaria, which has gone through numerous socioeconomic transformations which have had their impact on the low participation levels and the subsequent public health problems. Sport development strategies, legislation and public announcements have been reviewed to determine the orientation of national sport policy. The primary research adopted a qualitative approach using a multiple case study design. Six semi-structured interviews have been conducted in order to get up-to-date information on current developments, challenges and future prospects in sport policy. Interviewees consisted of three municipality representatives, one central government official, and two non-government sport-for-all organisations (NGOs) officers. The concept of Bourdieu’s Habitus and the Multiple Streams framework have been utilized as theoretical frameworks to analyse sport participation and sport policy, respectively, with the focus being on the latter. The key priority in Bulgarian sport policy appeared to be youth competitive sport. A variety of issues were pointed out by municipalities but a common feature was the limited resources. Some gave a critical self-reflection on the need to give more attention to certain age groups such as the elderly. All three municipalities had their own policy activities implemented which signalled for good level of autonomy. A commonality was the provision of heavily discounted or free municipal sports facilities to clubs and citizens. Differences included emphasis on promoting elite sport within one municipality and enhancing sport for all in another. Cooperation with the ministry was described as good although, surprisingly, this was not the case in Sofia, where the ministry is based. Two municipalities appeared heavily involved in cooperating with NGOs and other institutions such as schools. To optimise sport policy in Bulgaria, cross-sectoral work should be enhanced, communication between the national and local authorities and between the ministry and the third sector should be improved. Stronger voice should be given to NGOs in the policy-making process as they have close contact with citizens and fresh ideas. The country’s limited resources need to be taken into account and a more strategic and realistic goals need to be put in place in the context of hugely expensive elite sport globally and high rates of non-communicable diseases nationally, which can be reduced through higher sport participation rates.